ANALISIS OPTIMALISASI WEBSITE SEBAGAI PENINGKATAN STRATEGI PEMASARAN DI RUMAH SAKIT ”X” KOTA MALANG - Rahmawan, Agung Effi (Jurnal Administrasi Publik, 2024)
Analysis Of Website Optimization As An Improvement In Marketing Strategy At Hospital "X" Malang City In recent years, the trend to access social media via digital technology has increased. 4.62 billion people use social media and 4.95 billion global internet users are active, according to Hootsuite data. Social media is one of the best ways to interact with patients, especially those who have obstacles to obtaining health services. Marketing products or services using digital technology is called digital marketing. Search Engine Optimization (SEO),  social media, and email are some of the media used in digital marketing activities. “X” Hospital in Malang City has used various digital platforms for marketing such as websites, Instagram, Facebook, Tiktok and WhatsApp. The current website development process is still considered not optimal. This can be seen from the fact that the Official “X” Hospital in Malang City Website is still not read as an active website in Google's algorithm, so the search results on the search page are not yet at the top or at least in the top 10 of Google's scores.